The demand of premium insurance in Malaysia / Nur Nazehatul Najeehah Mohd Kasbi - Mohd Kasbi, Nur Nazehatul Najeehah (2016)
The objectives of this study is to examine and investigated relationship between two variables which is dependent variables and independent variables. From my study ,there are four independent variables which is Tax Considerations, income, Leverage and Growth opportunities. AII these independent variable will affect the dependent variables. My dependent variables is demand of premium insurance. This research is about the relationship between the demand of premium insurance and all the independent variables from 1983 to 2014 by using yearly data. The data was analyzed by using time series data and had been tested for several statistic. These findings has been proved by four independent variables. This study also comes out with several conclusion and recommendation for future research.